Canadian bank balance-sheet management: Breakdown by types of Canadian financial institutions - David Xiao Chen; H. Evren Damar; Hani Soubra; Yaz Terajima (Bank of Canada, 2012)
The authors document leverage, capital and liquidity ratios of banks in Canada. These ratios are important indicators of different types of risk with respect to a bank's balance-sheet management. Particular attention is given to the observations by different types of banks, including small banks that historically received less attention. In addition, the authors compare leverage and capital ratios for banks in Canada and the United States in the period leading up to the recent crisis. They find that in Canada, most of the risks indicated by these balance-sheet ratios are concentrated among large banks that are more likely able to withstand shocks due to their diversified portfolios. Some smaller banks, however, reveal vulnerability against liquidity risks. Regarding a Canada-U.S. comparison, small U.S. banks show more vulnerability than their larger counterparts, as well as an increasing trend in vulnerability prior to the crisis. In contrast, the ratios for small Canadian banks show increasing resilience.
Keywords: G21; G28; 330; Financial institutions; Financial stability; Financial system regulation and policies